Actual questions of intensiﬁcation of lipid-lowering therapy - Resolution of the National Scientific Council of Experts (The Journal of Atherosclerosis and Dyslipidemias, 2022)
Members of the Expert Council: Academician of the Russian Academy of Sciences S.A. Boytsov (Moscow), Academician of the Russian Academy of Sciences M.I. Voevoda (Novosibirsk), prof. V.S. Gurevich (St. Petersburg), prof. D.V. Duplyakov (Samara), M.V. Ezhov (Moscow), prof. Yu.A. Karpov (Moscow), V.V. Kashtalap (Kemerovo), prof. Nedogoda S.V. (Volgograd), prof. I.V. Sergienko (Moscow).